2020
DOI: 10.1111/jpm.12644
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 lockdown: A perfect storm for older people’s mental health

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
109
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(114 citation statements)
references
References 0 publications
1
109
0
4
Order By: Relevance
“… 48 Elderly people are at especially high risk of severe COVID-19 illness and mental-health-related consequences because they might already have some cognitive decline. 49 , 50 Institutions can become epicentres for infection. Physical distancing can be challenging in these contexts, either because the nature of patients' conditions makes it difficult to manage (eg, people with learning disabilities) or because of overcrowding (eg, prisons).…”
Section: Potential Consequences Of Covid-19 For Mental Healthmentioning
confidence: 99%
“… 48 Elderly people are at especially high risk of severe COVID-19 illness and mental-health-related consequences because they might already have some cognitive decline. 49 , 50 Institutions can become epicentres for infection. Physical distancing can be challenging in these contexts, either because the nature of patients' conditions makes it difficult to manage (eg, people with learning disabilities) or because of overcrowding (eg, prisons).…”
Section: Potential Consequences Of Covid-19 For Mental Healthmentioning
confidence: 99%
“…For instance, after lockdown, referrals accelerated again across genders. Unexpectedly, no such acceleration was observed among those aged ≤19 or ≥65, who have been suspected to be especially vulnerable to mental health problems resulting from social distancing or lockdown (10,12,(19)(20)(21), even though all age groups exhibited the significant instantaneous drop in referrals at lockdown. The lack of acceleration in referrals for older adults after lockdown was also to some extent inconsistent with a study (22) conducted in Hong Kong at the time of the severe acute respiratory syndrome (SARS) epidemic in 2003, which found SARS to be associated with a 30% increase in suicide in those aged ≥65.…”
Section: Discussionmentioning
confidence: 95%
“…Several studies conducted on people's mental health during lockdown or isolation reported restriction of movement showed that when people are restricted to a certain kind of environment, their mental health is adversely affected [10][11][12][13] . Historically, quarantine has been related to psychological outcomes such as anxiety, depression, panic, irritability, somatic disorder, and insomnia 14 .…”
Section: Introductionmentioning
confidence: 99%